Productive and income contributions of sheep, goat, and cattle, and different diversification schemes in smallholder production systems of Northern Patagonia, Argentina - Villagra, Edgar Sebastian; Easdale, Marcos Horacio; Giraudo, Celso Gabriel; Bonvissuto, Griselda (Springer, 2018)
Wool production oriented sheep keeping is the most important rural activity in Patagonia, Argentina, followed by goat and at a lower extent cattle production. The existing perception on the smallholder production systems from most decision makers (e.g., policy) is that they are marginal, with low productivity and have negative returns. Since the Argentinean economic scenario has changed drastically in the last decade, the aim of this study was to analyze the economic and productive contribution of different livestock species in smallholdings. The results showed that the post-1990’s economic scenario turned most smallholder livestock systems to have positive economic performance, but there were still productive restrictions that limited to fully benefit from these favorable circumstances. Goats were the most profitable livestock due to their higher productive performance, followed by sheep and cattle, with poorer performances. A strong cooperation between the intervention programs and research institutions is recommended to overcome the current production bottlenecks, by focusing on cattle and sheep production systems.